EFISIENSI PENGGUNAAN INPUT PRODUKSI USAHATANI PADI SAWAH ANTARA SISTEM IRIGASI TEKNIS DAN SISTEM POMPANISASI - pipih pipih; Aliudin Aliudin; Khaerul Saleh (JURNAL AGRIBISNIS TERPADU, 2020)
This research  to find out the magnitude of the effect of the use of inputs both simultaneously and partially and the level of price efficiency in the use of inputs in the technical  lowland rice farming in the Kasemen District and pumping systems in the Carenang District. Simple random sampling method as a method for sampling. The number of respondents for the technical irrigated paddy farmers in  Kasemen District was 44 farmers, and for the pumping paddy farmers in Carenang District the same amounted to 44 farmers. The data processing method is to use Cobb-Douglas production function analysis and price efficiency. Based on theresults of the study showed 1) in the F test (simultaneous), the use of land area, seeds, labor and urea fertilizer had a significant effect on the production of lowland rice both in Kasemen and Carenang Districts. 2) by t test (partial), the use of inputs that significantly influence the production of lowland rice in Kasemen District and in Carenang District namely urea fertilizer, land area and seeds. 3) The level of efficiency for technical irrigation systems is know to use land area inputs of 1.28 (not efficient), seeds of 18.55 (not efficient), labor of 0.11 (inefficient) and urea fertilizer of 14.45 (not efficient). Meanwhile, for pumping paddy farming, it is known that the level of efficiency of the use of inputs is land area of 3.22 (not efficient), seeds of 8.31 (not efficient), labor of 0.45 (inefficient) and urea fertilizer of 20.55 (not efficient).